2015
DOI: 10.3748/wjg.v21.i23.7134
|View full text |Cite
|
Sign up to set email alerts
|

Review of a challenging clinical issue: Intrahepatic cholestasis of pregnancy

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a reversible pregnancy-specific cholestatic condition characterized by pruritus, elevated liver enzymes, and increased serum bile acids. It commences usually in the late second or third trimester, and quickly resolves after delivery. The incidence is higher in South American and Scandinavian countries (9.2%-15.6% and 1.5%, respectively) than in Europe (0.1%-0.2%). The etiology is multifactorial where genetic, endocrine, and environmental factors interact. Maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 58 publications
1
129
0
10
Order By: Relevance
“…The Cochrane Review found that there was support for UDCA for the relief of maternal pruritus (Gurung et al, 2013;Saleh & Abdo, 2007) and restoring bile acids to a normal state (Saleh & Abdo, 2007), by increasing the biliary secretion that lowers the toxic bile salts, bilirubin (Gabzdyl & Schlaeger, 2015) and liver enzymes in maternal blood (Ozkan et al, 2015). This is further substantiated by a meta-analysis including non-randomized studies conducted by Grand'Maison et al (2014).…”
Section: Pharmacological Treatment Of Icpmentioning
confidence: 96%
See 2 more Smart Citations
“…The Cochrane Review found that there was support for UDCA for the relief of maternal pruritus (Gurung et al, 2013;Saleh & Abdo, 2007) and restoring bile acids to a normal state (Saleh & Abdo, 2007), by increasing the biliary secretion that lowers the toxic bile salts, bilirubin (Gabzdyl & Schlaeger, 2015) and liver enzymes in maternal blood (Ozkan et al, 2015). This is further substantiated by a meta-analysis including non-randomized studies conducted by Grand'Maison et al (2014).…”
Section: Pharmacological Treatment Of Icpmentioning
confidence: 96%
“…Maternal outcomes are benign, however, ICP can result in preterm labour, meconium staining, fetal distress and fetal demise (Ozkan et al, 2015) with the greatest to the fetus identified after 37 weeks (Bull et al, 2015). The severity of a case of ICP is defined according to the level of bile acids.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…74,75 Şu ana kadar GİK hastalarının izlem ve tedavisinde kesin bir protokol oluşturulamamıştır ve en uygun doğum yaşı için net bir kılavuz yoktur.…”
Section: Gebeli̇ği̇n İntrahepati̇k Kolestazinda Hasta Yöneti̇mi̇unclassified
“…Intrahepatic cholestasis of pregnancy (ICP) is a liver disorder during pregnancy. The incidence of ICP varies geographically from .2 to 2%, being most common in South America and northern Europe . It typically manifests at the late second or third trimester of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%